Isolated Myeloperoxidase–Antineutrophil Cytoplasmic Antibody–Associated Hypertrophic Pachymeningitis. Issue 3 (April 2022) - Maneval, Jeffrey; Bryant, Bronwyn; Ulano, Adam; Waheed, Waqar; Nevares, Alana
Abstract: A 65-year-old man with no pertinent medical history presented with 1 month of progressive holocephalic positional headaches (worse supine), photophobia, progressive gait instability resulting in multiple falls (ambulatory to walker in only 2 months), and weight loss. Testing found positive ANCA 1:160 perinuclear patter, myeloperoxidase >8.0. Cerebrospinal fluid found lymphocytic pleocytosis. We present his neuroimaging of isolated hypertrophic pachymeningitis with clinicoradiographic resolution after immunomodulatory pharmacotherapy along with histology from his meningeal biopsy. Isolated vasculitic myeloperoxidase–antineutrophil cytoplasmic antibody hypertrophic pachymeningitis is quite rare.